URGENSI PERSYARATAN UNTUK MASYARAKAT HUKUM ADAT DALAM RUU PERTANAHAN - Sukirno Sukirno (Masalah-Masalah Hukum, 2013)
Criteria for the recognition of indigenous people with the condition, viewed from any point of view, both techniques Jegislaoon, Pancasila as the guiding principle in the formation of law, human rights, the realities on the ground, expert opinion, as well as national and international legal instruments, the recognition of indigenous peoples and their rights to certain requirements are not urgent, even going to hinder the achievement of one of the country's goal to promote the general welfare (including indigenous peoples) as stated in the preamble of the 1945 NRI Constitution.